Kebijakan Sustainable Forest Management Sebagai Bagian Indonesia’S Folu Net Sink 2030 - Hirma Parimita; Fatma Ulfatun Najicha (Simbur Cahaya, 2023)
This study aims to determine the policies taken by the Government of Indonesia as a party to the Paris Agreement related to efforts to reduce greenhouse gas (GHG) emissions. This legal research is normative legal research using a conceptual approach that is based on the development of views and doctrines in the science of law. The legal materials used are primary and secondary legal materials collected through library research techniques and analyzed using the deduction method. The results of this study indicate that Indonesia carries out constant GHG emission reductions as stated in the Nationally Determined Contribution (NDC). One of the sectors with the largest proportion of GHG emission reductions in Indonesia's NDC is the forestry sector, so forestry mitigation is vital for Indonesia. Forestry and Other Land Use (FOLU) is a component of the NDC which is targeted to contribute 60% of the total GHG reduction. The implementation of Indonesia's FOLU Net Sink 2030 is based on the Sustainable Forest Management (SFM) component where sustainable and sustainable forest management is a big task to be implemented and regulated carefully and wisely so that the GHG emission reduction target contained in the NDC can be achieved and can reach net zero emissions in 2060.